Examining the impact of peacekeeping and peace enforcement in Democratic Republic Congo-the cases of Operation Artemis 2003 and Force intervention Brigade 2013 - Kandowe, William (My University, 2019)
This study set out to examine how effective peace enforcement mechanism of peacekeeping missions has been in conflict-ridden countries, in Sub-Saharan Africa (SSA). Consequently these conflicts have led to various interventions, including the adoption of both peacekeeping and peace-enforcement strategies in an attempt to resolve conflicts. However, in the face of humiliation of peacekeeping forces and the continuation of human suffering, there has often been the need to change the mandate of the forces to that of enforcement. The study adopts a mixed method approach – using both qualitative and quantitative methodologies. It makes use of a case study method to examine the implementation of peacekeeping in SSA. In addition this study used quantitative data to examine the effectiveness of peacekeeping missions in the region. The focus of this study was on the European Union‘s (EU) Operation Artemis and the United Nations‘ (UN) FIB, activity in the Eastern Democratic Republic Congo (DRC) to determine their effectiveness in keeping peace in the region. Peacekeeping missions are defined as techniques designed purportedly to ensure peace returns in previously hostile societies. The use of force is considered as the last resort in the UN Charter. The abovementioned operations have continually used force in an attempt to keep peace in the Eastern DRC. Irrespective of the missions‘ effort, conflict still recurs in the region. The findings of this research show that colonialism, ethnic division, differences over ancestral land, marginalization, greed and grievances are at the core of the conflict in Ituri and the 2013 M23 rebellion. This finding is consistent with that of the literature. The research set out to explain and analyse the political and economic complexities of the on-going Ituri crisis, between Lendu agriculturalists and pastoralist Hema ethnic groups. The literature on conflict and peacekeeping missions in SSA, particularly the Eastern DRC claims that debates around the use of force leans towards stronger support for offensive operations being more successful in achieving peace than non-offensive operations. An example of this is the UN‘s loss of the city of Goma, which M23 rebels took over with little resistance from the peacekeepers. This thesis concludes that Operation Artemis of 2003 and Force Intervention Brigade 2013 are two interventions built upon and sought to address the limits of the lager UN peacekeeping missions in the DRC.
Research submitted to the Faculty of Humanities in fulfilment of the requirements of the Master‘s Degree in International Relations, University of the Witwatersrand, Johannesburg South Africa, 2019